Inclusión económica y social de las mujeres privadas de libertad - Pinos Calderón, Doris Elena (2014)
In this research the scope of the main proposals of economic and social inclusion made in the period 2012-2013 to rehabilitate the inmates of Social Rehabilitation Center is determined Women of Quito. The purpose of reviewing the implications caused by the rehabilitation effort of the state, on the lives of women and their reintegration into society, is related to the analysis of a structural exclusion that not only permeates the crime, but the impoverished and criminaliz to in and out of prison space.